Individual Differences in Children's Pragmatic Ability: A Review of Associations with Formal Language, Social Cognition, and Executive Functions. Issue 3 (3rd July 2018) - Matthews, Danielle; Biney, Hannah; Abbot-Smith, Kirsten
ABSTRACT: Children vary in their ability to use language in social contexts and this has important consequences for wellbeing. We review studies that test whether individual differences in pragmatic skill are associated with formal language ability, mentalizing, and executive functions in both typical and atypical development. The strongest and most consistent associations found were between pragmatic and formal language. Additional associations with mentalizing were observed, particularly with discourse contingency and irony understanding. Fewer studies considered executive function and evidence is mixed. To make progress, high-quality studies of specific pragmatic skills are needed to test mechanistic models of development. We propose six goals for future research: (1) developing an empirically based taxonomy of pragmatic skills; (2) establishing which skills matter most for everyday functioning; (3) testing specific hypotheses about information processing; (4) augmenting measures of individual differences; (5) considering a broader set of psychological associates; and (6) employing statistical tools that model the nested structure of pragmatics and cognition.